2000
DOI: 10.1148/radiology.214.2.r00fe05411
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Sarcoidosis: Follow-up at MR Imaging during Steroid Therapy

Abstract: MR imaging can be used to differentiate between reversible and irreversible lesions in CNS sarcoidosis. MR imaging can be a useful tool for adjusting treatment to prevent irreversible CNS damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 35 publications
2
43
0
5
Order By: Relevance
“…Sarcoid myelopathy may mimic multiple sclerosis, tumor, vacuolar myelopathy, tuberculosis, and fungal infections. 14,20,23 Similar to findings in previous reports, 13,14 we did not find any correlation between nonenhancing white matter lesions with clinical symptoms. These lesions also did not demonstrate any response to therapy and may also be seen in patients who do not have sarcoidosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sarcoid myelopathy may mimic multiple sclerosis, tumor, vacuolar myelopathy, tuberculosis, and fungal infections. 14,20,23 Similar to findings in previous reports, 13,14 we did not find any correlation between nonenhancing white matter lesions with clinical symptoms. These lesions also did not demonstrate any response to therapy and may also be seen in patients who do not have sarcoidosis.…”
Section: Discussionsupporting
confidence: 89%
“…8,13,14 In this study, we analyzed clinical and radiologic records of patients with biopsyproved or clinically diagnosed neurosarcoidosis for the following reasons: 1) to assess the concordance between abnormalities noted on MR imaging with neurologic symptoms at presentation; 2) to correlate changes in imaging findings during follow-up with clinical improvement or worsening; and 3) to identify imaging features that may have prognostic significance.…”
mentioning
confidence: 99%
“…Corticosteroids are the therapy of choice as they have been reported to improve neurological symptoms and reduce intracranial sarcoid spread confirmed by MRI [16,17,18]. In our case, corticosteroids therapy was effective and revealed an obvious decrease of the lesion size.…”
Section: Discussionsupporting
confidence: 55%
“…MRI is an important tool in monitoring the course of neurosarcoidosis and its response to therapy (13). By means of MRI, it is confirmed that corticosteroid generally improves the neurological symptoms and causes reduction in intracranial sarcoid spread.…”
Section: Discussionmentioning
confidence: 97%